COMMUNICATIVE APPROACH IN TEACHING PHRASEOLOGICAL UNITS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article explores the integration of the communicative approach in the teaching of phraseological units, encompassing idioms, collocations, and fixed expressions. It emphasizes moving beyond rote memorization to practical application in authentic communication. The advantages discussed include contextual understanding, cultural relevance, and increased retention. Practical strategies such as role-playing activities, interactive discussions, authentic texts, and technology integration are highlighted to facilitate effective implementation. The article underscores the importance of not only learning phraseological units but also using them in culturally appropriate ways. Educators are encouraged to adopt a dynamic approach, integrating technology and real-world experiences to create a communicative language learning environment that fosters practical application and cultural understanding.